The pricing of European non-performing real estate loan portfolios: evidence on stock market evaluation of complex asset sales - Florian Manz; Birgit Müller; Dirk Schiereck (Journal of Business Economics, 2020)
Recent empirical evidence raises doubt about the ability of financial market participants to generate information efficient valuations for capital market instruments whose cash flows are related to residual claims and dependent on real estate income. We contribute to this literature with the examination of value implications of non-performing loan (NPL) divestitures in the banking industry during the period 2012–2018. In a first step, we provide descriptive statistics of the European NPL market, which lacks transparency and publicly available basic information on portfolio size and components. We then analyze wealth effects of distressed loan sale announcements for a uniquely large transaction database with 317 NPL deals, which is largely driven by real estate collateral. Our results show positive stock market reactions for vendor banks following NPL divestitures that tend to be driven by real estate collateral and a size effect.
Keywords: G14; G21; R32; 650; Non-performing loans; Distressed real estate; Restructuring; Banking sector; Real estate finance